ANALISIS PENDAPATAN ASLI DAERAH , BELANJA MODAL DAN DANA ALOKASI UMUM (DAU) TERHADAP PERTUMBUHAN EKONOMI DI PROPINSI KALIMANTAN BARAT - B61108002, PRANTINI (Jurnal Ekonomi Daerah (JEDA), 2014)
ABSTRACT By increasing the local revenue, the economic activity in West Kalimantan will rises and so does the economic growth. It’ll also have the same impact on capital expenditure. it’s important to analyze the market development of the local revenue in West Kalimantan so we will know how the local revenue impact on the economic growth. There’s positif significant relation from capital expenditure and non linear general allocation fund to economic growth in West Kalimantan. On the other hand, the local revenue has the negative impact. Unlike the local revenue development, value of government capital expenditure increase for years. Keywords: PAD, DAU, singnifikan, economic growth